2016
DOI: 10.1093/bioinformatics/btw369
|View full text |Cite
|
Sign up to set email alerts
|

Assemblytics: a web analytics tool for the detection of variants from an assembly

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
353
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(353 citation statements)
references
References 6 publications
0
353
0
Order By: Relevance
“…SNPs and small indels were then identified if they were supported by at least four mapped reads. To detect large SVs (≥50 bp), genome sequences of ‘97103’ and ‘Charleston Gray’ were aligned using Minimap2 (Li, ), and based on the alignment indels and tandem/repeat expansions/contractions were identified using Assemblytics (Nattestad and Schatz, ). To confirm the identified SVs, reads generated from one genome were aligned to the opposite genome using bowtie (Langmead et al ., ) allowing one mismatch.…”
Section: Methodsmentioning
confidence: 99%
“…SNPs and small indels were then identified if they were supported by at least four mapped reads. To detect large SVs (≥50 bp), genome sequences of ‘97103’ and ‘Charleston Gray’ were aligned using Minimap2 (Li, ), and based on the alignment indels and tandem/repeat expansions/contractions were identified using Assemblytics (Nattestad and Schatz, ). To confirm the identified SVs, reads generated from one genome were aligned to the opposite genome using bowtie (Langmead et al ., ) allowing one mismatch.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Assemblytics (Nattestad and Schatz, 2016) . In plants, population analysis of 302 soybean re-sequencing lines showed that many CNVs could be targets of artificial selection in addition to the SNPs.…”
Section: Algorithmic Advancement To Detect Structural Variationsmentioning
confidence: 99%
“…We analyzed the resulting alignment using Assemblytics [12], with results available at: http://assemblytics.com/analysis.php?code= human. We also downloaded the MHAP CHM1 assembly (accession: GCA 000772585)…”
Section: Supplementary Note 3 Obtaining Chm1-specific Sequencesmentioning
confidence: 99%
“…We analyzed the resulting alignment using Assemblytics [12], with the results available at: http://assemblytics.com/ analysis.php?code=sIOvqHUKNaCpU8NXdcTS. This assembly is like the one used above (accession: GCA 000772585), but with low-support contigs (having fewer than 50 supporting reads) removed.…”
Section: Supplementary Note 3 Obtaining Chm1-specific Sequencesmentioning
confidence: 99%
See 1 more Smart Citation